Additive effects of touch-activated polymerization and extended irradiation time on bonding of light-activated adhesives to root canal dentin - Dwiandhany, Wahyuni S; Abdou, Ahmed; Tichy, Antonin; Yonekura, Kazuhide; Ikeda, Masaomi; Hosaka, Keiichi; Tagami, Junji; Nakajima, Masatoshi (The Journal of prosthetic dentistry, 2022)
STATEMENT OF PROBLEM: The bonding of light-activated adhesives to root canal dentin with an additional touch-polymerization activator has been insufficiently examined. PURPOSE: The purpose of this in vitro study was to investigate the effect of touch-polymerization activators and extended light-irradiation time on the microtensile bond strength (μTBS) of light-activated adhesives. MATERIAL AND METHODS: Post cavities were prepared in 50 extracted mandibular premolars and bonded using Prime&Bond Universal (PBU); PBU+Self Cure Activator (SCA); Clearfil SE Bond 2 (SEB); SEB+Clearfil DC Activator (DCA); or Clearfil Universal Bond Quick ER (UBQ). After light-irradiation for 10 or 20 seconds, the post cavities were filled with dual-activated resin core materials. Eight beams were prepared per specimen and subjected to the μTBS test. The μTBS data were analyzed by using 3-way ANOVAs with the Bonferroni correction (α=.05). RESULTS: The 3-way ANOVAs indicated that the use of touch-polymerization activators (SCA and DCA) significantly increased the μTBS of PBU and SEB in both the coronal (P=.015) and apical (P=.001) regions. The extension of light-irradiation time to 20 seconds significantly improved their μTBS in the apical region (P<.001), but not in the coronal region (P=.09). Light-irradiation for 20 seconds increased the μTBS of UBQ significantly in the coronal region (P=.014). CONCLUSIONS: Touch-polymerization activators improved the bond strength of light-activated adhesives to root canal dentin, especially when combined with an extended light-irradiation time.
Keywords: kavita zubní dřeně; Composite Resins; Resin Cements; Touch; Tensile Strength; Dentin-Bonding Agents; testování materiálů; hmat; Dentin; pryskyřičné cementy; Polymerization; polymerizace; vazba zubní; Dental Pulp Cavity; zubní cementy; složené pryskyřice; Dental Bonding; dentinová adheziva; pevnost v tahu; Dental Cements; Materials Testing; dentin